2013
DOI: 10.1371/journal.pone.0084934
|View full text |Cite
|
Sign up to set email alerts
|

MMP Mediated Degradation of Type IV Collagen Alpha 1 and Alpha 3 Chains Reflects Basement Membrane Remodeling in Experimental and Clinical Fibrosis – Validation of Two Novel Biomarker Assays

Abstract: ObjectivesFibrosis is characterized by excessive tissue remodeling resulting from altered expression of various growth factors, cytokines and proteases. We hypothesized that matrix metalloproteinase (MMP) mediated degradation of type IV collagen, a main component of the basement membrane, will release peptide fragments (neo-epitopes) into the circulation. Here we present the development of two competitive enzyme-linked immunosorbent assays (ELISAs) for assessing the levels of specific fragments of type IV coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(151 citation statements)
references
References 59 publications
4
141
0
Order By: Relevance
“…Tumor cells overproduce MMP-9, leading to the degradation of type IV collagen and the basement membrane, which disrupts tissue architecture and function (55). The present findings are consistent with previous studies, which suggested that MMP-9 plays a role in bladder cancer (56,57).…”
Section: A B Csupporting
confidence: 92%
“…Tumor cells overproduce MMP-9, leading to the degradation of type IV collagen and the basement membrane, which disrupts tissue architecture and function (55). The present findings are consistent with previous studies, which suggested that MMP-9 plays a role in bladder cancer (56,57).…”
Section: A B Csupporting
confidence: 92%
“…C4M reflects basement membrane (BM) remodeling and invasion, and measures a type IV collagen a1-chain fragment generated by cleavage with MMP-12 (7). A hallmark of the malignant process is the acquisition of an invasive phenotype that enables malignant cells to invade the BM (13).…”
Section: Introductionmentioning
confidence: 99%
“…Using well-characterized and validated competitive ELISAs, levels of MMP 2, 9 and 13-degraded collagen type I (C1M) [10], MMP-9 degraded collagen type III (C3M) [11], and MMP-9 and 12 degraded collagen type IV (C4M, C4M12) [12,13] were assessed in the serum samples.…”
Section: Elisa Measurements and Proceduresmentioning
confidence: 99%